А model of managing the development of professional competence of teachers of the new Ukrainian school in the process of methodological work - Protsenko, I.; Bikova, M. (Problems of Engineer-Pedagogical Education, 2021)
The professional activity of a teacher of the New Ukrainian School is determined not only by the amount of educational tasks to be solved, but also by the significance of this period for the whole development and formation of the child's personality, values and worldview. The purpose of the article is to develop and experimentally test a management model for the development of professional competence of teachers of the New Ukrainian School in the process of in-school methodological work. In order to verify the effectiveness of the structural-logical model of managing the development of professional competence of primary school teachers in the process of in-school methodological work, purposeful observation of the activities of teachers of the New Ukrainian School and questionnaires were used; testing, pedagogical experiment, analysis of teachers' performance were conducted. In the presented research the developed model includes three basic blocks: target, managerial, and diagnostic-corrective. Each of these blocks consists of the main components: the target block determines the purpose and objectives of the management process of professional competence formation of the New Ukrainian school teachers; the managerial block reflects the scientific approaches, conditions of formation, stages of implementation of the model, methods, tools, principles and leading ideas; the diagnostic-corrective block reflects the criteria and levels of professional competence. The model has the following stages: target, prognostic, productive-creative, and final. The criteria for identifying the level of management of professional competence development are determined: awareness of artifacts; awareness of the system of orders; management of the system of values in professional activity, understanding of the system of knowledge; essence, structure, content and technologies of professional activity of a teacher of the New Ukrainian school.